PELATIHAN PEMBUATAN PUPUK DAN BIOPORI UNTUK PENINGKATAN RESAPAN AIR DAN KESUBURAN TANAMAN PERTANIAN DI DESA KURUNG KAMBING KEC.MANDALAWANGI KABUPATEN PANDEGLANG - Sodikin Sodikin; Shinta Permana Putri; Guntur Bagus Pamungkas; Nurhasanah Nurhasanah; Ila Fadila (LPPM Institut Pendidikan Nusantara Global, 2026)
This community service program was implemented in Kurung Kambing Village, Mandalawangi District, Pandeglang Regency, which faces the problem of declining soil fertility due to dependence on chemical fertilizers and low water absorption capacity, which causes flooding during the rainy season and drought during the dry season. This activity aims to increase the community's capacity to apply environmentally friendly agricultural technologies through training in the production of liquid organic fertilizer (POC) containing phytohormones and biopore infiltration holes. The implementation method was carried out in three stages: preparation, training, and evaluation. The training materials included the theory and practice of making POC from local ingredients such as shallots and corn, as well as techniques for creating and maintaining biopores for water conservation. The program was actively participated in by the community and local farmer groups through demonstrations and field practice. Evaluation results showed that participants were able to produce POC independently and apply biopore technology to their agricultural land. Most participants demonstrated an increased understanding of soil fertility management and water conservation, and reported improved plant growth and increased crop productivity compared to before the training. The application of biopores also provided tangible benefits in the form of reduced waterlogging during the rainy season and maintained soil moisture during the dry season. In addition to improving the technical aspects of cultivation, this program has successfully increased community awareness, independence, and confidence in adopting sustainable agricultural technologies. Thus, the integration of phytohormone-enriched Liquid Organic Fertilizer (POC) and biopores provides a simple, locally resource-based technology that is effective in supporting agricultural resilience and environmental conservation at the village level.